PENGARUH ACTIVE PARTICIPATION , EXPERIENCE SHARING DAN CONSUMER SATISFACTION TERHADAP CONSUMER HAPPINESS - Ega Hilal Fauzi; Aekram Faisal (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to analyze the effect of Active Participation, Experience Sharing, and Consumer Satisfaction on Customer Satisfaction of Warung Kopi Kopi Kenangan, Kopi Janji Jiwa, Kopi Kulo and Kopi Fore customers. This research is a quantitative research using primary data. The sampling procedure used to collect relevant data is by using a questionnaire and using a purposive sampling method. This research was conducted on 150 respondents who met the criteria determined by the researcher. The data analysis method used in this study is to analyze the effect of the variables owned by using the Structural Equation Model (SEM) and using the SPSS application. The results of this study indicate that Active Participation, Experience Sharing, and Consumer Satisfaction have a positive influence on Consumer Pleasure.